Global Trends in Cyberlaw and Online Ads: A Data Analysis - Octaviani, Tresnia; Multazam, Mochammad Tanzil; Hasan, Rizqi (Proceedings of The ICECRS, 2023)
This data article examines the landscape of cyberlaw research through a comprehensive analysis of journal articles focused on "cyberlaw" and "online ads." Utilizing Lens.org, articles within the "law" subject category were filtered and exported in CSV and BibTeX formats. The study identifies prolific contributors, active countries, and prominent publishers in this field, shedding light on the scholarly output. Additionally, it evaluates the efficacy of four warning banners in mitigating distributed denial-of-service attacks, underscoring the significance of user awareness in combating online threats. The findings highlight the dynamic nature of cyberlaw and its pivotal role in addressing contemporary online challenges.Higlights : Research Landscape: Reveals contributors, active countries, and publishers in cyberlaw research. User Awareness in Threat Mitigation: Evaluates warning banners' efficacy against cyberattacks. Dynamic Nature of Cyberlaw: Highlights its crucial role in addressing evolving online challenges. Keywords: Cyberlaw, Online Ads, Scholarly Output, User Awareness, Online Threats